Relationship Between Stress Level and Sleep Quality with Primary Dysmenorrhea in Female Students of SMAN 19 Surabaya - Arum Ariasty, Aurelya; Sri Rejeki, Purwo; Setyowati, Dewi (Rifa'Institute, 2025)
Introduction: Primary dysmenorrhea, or menstrual pain without underlying pathological conditions, is the most common reproductive health disorder experienced by adolescents. The global prevalence of primary dysmenorrhea reaches 66.1%. Lifestyle factors may influence the occurrence of dysmenorrhea. Objective: This study aims to analyze the relationship between stress levels and sleep quality with primary dysmenorrhea among female students at SMAN 19 Surabaya. Methods: This study employed a quantitative approach with an analytical observational design. The research design used was cross-sectional. The population consisted of 10th- and 11th-grade female students of SMAN 19 Surabaya. A total of 217 samples were obtained using stratified sampling. Data were collected through questionnaires and analyzed using the Spearman Rank test (α < 0.05). Results and Discussion: The Spearman Rank analysis showed a significant relationship between stress levels and primary dysmenorrhea, with a p-value of < 0.001 (p < 0.05). A significant relationship was also found between sleep quality and primary dysmenorrhea, with a p-value of < 0.001 (p < 0.05). Conclusion: There is a relationship between stress levels and sleep quality with primary dysmenorrhea among female students at SMAN 19 Surabaya.